Perubahan Berat Badan Selama Pengobatan Tuberkulosis Paru - Ladies Nursyfah; Heni Muflihah (UNISBA Press, 2023)
Abstract. Tuberculosis (TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis (MTB). TB patients usually experience malnutrition, which is characterized by weight loss (BB). Leptin levels that regulate body weight change during TB treatment. The purpose of this study was to determine the difference in changes in body weight after the initial and advanced stages of treatment in patients. This study used an analytic observational method with a cross-sectional design with secondary data on adult pulmonary TB patients at the Cidempet Health Center, Indramayu Regency using a purposive sampling technique. Data on body weight during TB treatment were analyzed descriptively and differences in body weight were analyzed using the dependent T test. The results of this study were obtained from a total of 138 subjects who had an average weight at diagnosis of 48.92 kg, after initial treatment 49.48 kg and after further treatment had an average of 51.29 kg. There is a difference in changes in body weight at the end of the initial stage of treatment compared to the advanced stage with a p-value of 0.000 (<0.005). The conclusion of this study is that the increase in body weight of TB patients after the initial stage of treatment is higher than the increase in body weight after the advanced stage of treatment. Keywords: Treatment, Tuberculosis, Weight Abstrak. Tuberkulosis (TB) adalah penyakit kronik menular yang disebabkan oleh bakteri Mycobacterium tuberculosis (MTB). Pasien TB biasanya mengalami malnutrisi, yang ditandai dengan penurunan berat badan (BB). Kadar leptin yang mengatur BB mengalami perubahan selama pengobatan TB. Tujuan penlitian ini adalah untuk mengetahui perbedaan perubahan BB setelah pengobatan tahap awal dan tahap lanjutan pada pasien. Penelitian ini menggunakan metode observasional analitik dengan rancangan cross sectional dengan data sekunder penderita TB paru dewasa di Puskesmas Cidempet, Kabupaten Indramayu menggunakan teknik purposive sampling. Data BB selama pengobatan TB dianalisis secara deskriptif dan perbedaan BB dianalisis menggunakan uji T test dependent. Hasil penelitian ini didapatkan dari total subjek sebanyak 138 orang memiliki rata – rata BB pada saat diagnosis 48,92 kg, setelah pengobatan awal 49,48 kg dan setelah pengobatan lanjutan memiliki rata – rata 51,29 kg. Terdapat perbedaan perubahan BB pada akhir pengobatan tahap awal dibandingkan tahap lanjutan didapatkan nilai p-value sebesar 0,000 (<0,005). Kesimpulan penelitian ini adalah peningkatan BB pasien TB setelah pengobatan tahap awal lebih tinggi daripada peningkatan BB setelah pengobatan tahap lanjutan. Kata kunci: Berat badan, Pengobatan, Tuberkulosis